2019
DOI: 10.1371/journal.pone.0215520
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale detection of hierarchical community architecture in structural and functional brain networks

Abstract: Community detection algorithms have been widely used to study the organization of complex networks like the brain. These techniques provide a partition of brain regions (or nodes) into clusters (or communities), where nodes within a community are densely interconnected with one another. In their simplest application, community detection algorithms are agnostic to the presence of community hierarchies: clusters embedded within clusters of other clusters. To address this limitation, we exercise a multi-scale ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 135 publications
(238 reference statements)
3
47
0
Order By: Relevance
“…More broadly, our results are consistent with a hierarchical control of information processing in the brain (Mearns et al, 2019; Deco and Kringelbach, 2017; Ashourvan et al, 2019; Park and Friston, 2013; Botvinick, 2008). Behavioral state changes slowly and reflects the animal’s broad behavioral goal (Wiltschko et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…More broadly, our results are consistent with a hierarchical control of information processing in the brain (Mearns et al, 2019; Deco and Kringelbach, 2017; Ashourvan et al, 2019; Park and Friston, 2013; Botvinick, 2008). Behavioral state changes slowly and reflects the animal’s broad behavioral goal (Wiltschko et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…This phenomenon is reported for an adaptive network of Morris-Lecar bursting neurons with spike-timing-dependent plasticity rule 21 . In addition, the role of hierarchy and modularity in brain networks has been discussed recently [22][23][24][25][26] . Both features therefore seem to play a key role for real-world neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, random walks are the basis of Infomap (Rosvall & Bergstrom, 2008), a popular method for detecting community structure in complex networks. Past studies of anatomical and functional brain connectivity have found interlinked communities that form a partly decomposable modular architecture (Ashourvan, Telesford, Verstynen, Vettel, & Bassett, 2019; Meunier, Lambiotte, Fornito, Ersche, & Bullmore, 2009). Such architectures are hallmarks of complex systems and are thought to be of fundamental importance for understanding mental processing and cognition (Bola & Borchardt, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this work we selected sample entropy since it can quantify the amount of regularity and unpredictability of fluctuations in a time series (Richman & Moorman, 2000). This is important because of the presence of communities in brain networks (Ashourvan et al, 2019; Meunier et al, 2009), which will result in repetitive patterns of nodes in the time series of the random walker’s movement (Fortunato & Hric, 2016).…”
Section: Discussionmentioning
confidence: 99%